A Resilient Health System in Response to Coronavirus Disease 2019: Experiences of Turkey - Keskinkiliç, Bekir; Shaikh, Irshad; Tekin, Ahmet; Ursu, Pavel; Mardinoglu, Adil; Mese, Emine Alp (Frontiers in Public Health, 2021)
Turkey’s response experience thus far with SARS-CoV-2 Pandemic affords the globe and the region a unique opportunity and distinctive insights for combating this novel virus. Pandemic response with one of the lowest case fatality ratio (2.8%; and 52.5/M population), particularly among the elderly (the high risk group) on one hand while rising to the occasion to shoulder its long standing global solidarity and humanitarian support provider role by providing personal protective equipment, globally scarce, to many countries in their desperate time of fight against pandemic on the other while still meeting the critical domestic needs stands out. This paper aims to highlight key decisions, actions, and partnerships behind Turkey’s successful fight against SARS-CoV-2 pandemic that have enabled her, turn the corner and components of its success story.